Plant Responses and Tolerance to Salt Stress: Physiological and Molecular Interventions - Hasanuzzaman, Mirza; Fujita, Masayuki (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Overall, the 19 contributions in this Special Issue "Plant Responses and Tolerance to Salt Stress: Physiological and Molecular Interventions" discuss the various aspects of salt stress responses in plants. It also discusses various mechanisms and approaches to conferring salt tolerance on plants. These types of research studies provide further directions in the development of crop plants for the saline environment in the era of climate change.